Product markets and paychecks: deregulation's effect on the compensation structure in banking - Abigail Wozniak (Institute for the Study of Labor (IZA), 2006)
This paper asks how deregulation intended to promote competition in the commercial banking industry affected the compensation structure for banking employees. Using establishment-based data from the Employment Cost Index Survey of the U.S. Bureau of Labor Statistics, I obtain measures of the level and distribution of wage and benefits compensation within industries. I then compare changes in compensation in the banking industry to changes in unaffected industries across states and over time to identify the effects of deregulation. Banking deregulation had no effect on compensation levels or inequality in the industry as a whole, but this masks conflicting changes within the compensation structure. Manager wages fell while non-manager wages held steady, leading to a large decline in between-occupation compensation inequality. In contrast, between-establishment inequality increased dramatically. Deregulation also led to increases in inequality among managers despite their falling wages and to significant shifts in the types of non-wage benefits banking employees received.
Keywords: J31; L11; 330; total compensation; compensation inequality; product market competition; commercial banking; Bankensystem; Deregulierung; Bankberufe; Vergütungssystem; Lohnstruktur; USA